Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 5 - Exponential Functions - 5.2 Solving Equations Using Exponent Rules - 5.2 Exercises: 60

Answer

$k = 3$

Work Step by Step

$4(3^{k}) - 40 = -6(3^{k}) + 230$ $4(3^{k}) + 6(3^{k}) = 230 + 40$ $(4+6)(3^{k}) = 270$ $10(3^{k}) = 270$ $3^{k} = 27$ $3^{k} = 3^{3}$ $k = 3$ Check: $4(3^{k}) - 40 \overset{?}{=} -6(3^{k}) + 230$ $4(3^{3}) - 40 \overset{?}{=} -6(3^{3}) +230$ $4(27) - 40 \overset{?}{=} -6(27) + 230$ $108 - 40 \overset{?}{=} -162 + 230$ $68 = 68$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.